Efektivitas Pembelajaran Daring Melalui Aplikasi Zoom dan Google Classroom di Universitas Muhammadiyah Sumatera Utara - Aminah Hanum; Rahma Ayu; Riani Riani (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine the effectiveness of online learning using the Zoom and Google Classroom applications during the COVID-19 pandemic at Muhammadiyah University, North Sumatra. This type of research is a qualitative research with a descriptive approach. The data sources in this study were students of PAI class A2 Afternoon and the phenomena that occurred when the online learning process occurred. Collecting data in this study is observation, interviews, and documentation. Data analysis techniques use the Miles Huberman model. The research results show that learning using the Zoom application is less effective because it must be in a strong and stable network, wasting quota and expensive quota prices. The Google Classroom application is effective for submitting assignments, UTS and UAS. The WhatsApp application is most effectively used in online learning because it is easily accessible by students who live in rural areas.